Archaeometric analysis of architectural ceramics form the site “Khustiin bulag” Tuv province, Mongolia - Byambasuren, Suvd-Erdene; Lochin, Ishtseren; Saran, Tengis; Baatarjav, Orgil; Gelegdorj, Eregzen; Solongo, Saran (Proceedings of the Mongolian Academy of Sciences, 2020)
A series of architectural ceramics, including roof tiles and bricks from the excavation site at Khustyn Bulag, Mungunmorit soum, Tuv aimag (province) of Mongolia were subjected to detailed archaeometric analysis. We present here results of Fourier-transform infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM-EDS) and Thermogravimetric analysis (TGA) and their potential to determine the composition of brick samples from one excavation site, and their firing temperatures. In addition, yellow ochre, which is a natural earth rock pigment that contains hydrated iron oxide and represents the most common pigment of antiquity, was revealed at this excavation site. The mineral composition of ochres will be determined and the possible use of it will be discussed.